항암화학요법으로 유발된 만성 말초신경병증 환자의 한의학적 치험 1례 : 2년 이상 지속된 항암화학요법 유발 말초신경병증 치험 - 안유민; 이유나; 백경민; 장우석; An, Yu-min; Lee, Yoo-Na; Baek, Kyungmin; Jang, Woo-Seok (대한한방내과학회지, 2020)
Objective: This study reports the effect of Korean traditional medicine on persistent chemotherapy-induced peripheral neuropathy (CIPN). Methods: The patient was treated with Korean traditional medicine that included acupuncture, moxibustion, and herbal medicine. The effectiveness of the treatment was evaluated by the Quality of Life Questionnaire-Core 30 (QLQ-C30), the Quality of Life Questionnaire Chemotherapy-Induced Peripheral Neuropathy (QLQ-CIPN20), the Medicinae Doctor Anderson Symptom Inventory (MDASI), and a numeral rating scale (NRS). We also used the Beck Depression Inventory (BDI) to evaluate the patient's mood change after relieving the paresthesia. Results: After treatment, the symptoms were improved. Paresthesia decreased 80%p after Korean medicine treatment. Conclusions: According to this study, Korean traditional medicine can be an effective treatment for paresthesia in patients suffering from CIPN over 2 years.